Difference of Toxoplasma gondii antibodies between Thai and Austrian pregnant women - Yaowalark Sukthana (2018)
Toxoplasma gondii IgG and IgM antibodies of Thai and Austrian pregnant women were studied, in the same laboratory unit, by using the Sabin-Feldman dye test and ISAGA-IgM. In Thai pregnant women, IgG antibody was found in 21.7 %, mostly the IgG titers were low and all were negative for IgM antibody. Conversely in Austrian pregnant women, IgG antibody was found in 30.0% with high titer, and there were 19 (6.3%) cases positive for IgM antibody. The seropositivity of T. gondii IgG antibody in Austrian pregnant women was significantly higher than in Thai (p = 0.02) and the titers were much higher. Two possibilities are postulated to explain the data: it may be because Thai women were infected at a younger age than Austrian women, so they were in the chronic infection stage corresponding with their negativity of IgM antibody or it may be due to the difference of strain virulence of T. gondii from the different parts of the world.